Double Beam Instability for the Mercury Upstream Waves - Y. Narita; U. Motschmann; H. Comişel; D. Schmid (The Astrophysical Journal)
Mercury shock-upstream region is plasma physically of great interest, as the solar wind plasma may encounter two ion beams, forming a double-beam plasma system. Properties of the double-beam instability are studied semianalytically using the magnetoionic theory (cold plasma waves including beams), such as the unstable mode, the resonance wavenumbers, and the growth rates, for various beam configurations. The cold plasma wave theory supports the idea that both the foreshock ions and the pickup ions can potentially drive the right-hand beam instability, and moreover, the instability may run simultaneously for the two beam species. Further nonlinear wave evolution scenarios are discussed, such as independent parametric instabilities and driven wave–wave couplings causing low-frequency and high-frequency splits of the waves. The double-beam instability is testable against numerical simulations of the plasma waves as well as magnetic field observations by the MESSENGER spacecraft and the upcoming BepiColombo spacecraft.